PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS X MIPA 1 DI SMA NEGERI 8 GOWA - Disya Ananda Nur Magfirah, Disya; Rosdiana Ngitung; Syamsiah (Universitas Cokroaminoto Palopo, 2023)
This study aims to determine the increase in activity, motivation and student learning outcomes through the application of the Problem Based Learning (PBL) model in class X MIPA 1 at SMA Negeri 8 Gowa on the subject of Biology Scope. This type of research is Classroom Action Research (CAR) which consists of 2 cycles. The subjects in this study were students of class X MIPA 1 at SMA Negeri 8 Gowa. The type of research instrument used was an observation sheet on learning activities and a test of learning outcomes in the form of a multiple choice test of 30 items for each cycle on the Scope of Biology material. The data obtained were analyzed by descriptive statistics. The results showed that (1) there was an increase in the biology learning activity of class X MIPA 1 students at SMA Negeri 8 Gowa, namely classically from 48.31% increased to 63.68%; (2) there was an increase in biology learning outcomes for class X MIPA 1 students at SMA Negeri 8 Gowa, from 48.6% of students who completed to 94.3%. These results indicate that the application of the Problem Based Learning model can increase the activity and learning outcomes of students in class X MIPA 1 students at SMA Negeri 8 Gowa.